Conhecimento financeiro e aspirações educacionais na juventude: uma análise microeconométrica com base no PISA 2015 e 2018 - Sena, Felipe Saraiva Moreira de (2021)
This work presents two essays that deal with important and current themes related to the economics of education. The first trial investigated whether financial education courses (both in and out of school) can increase financial proficiency for 15-year-old students who took the standardized PISA 2015 test. The methodology used was that of Propensity Score Matching (PSM), controlling the characteristics observable at the level of students, family, and school. The results show that only the treatment “taking a course outside school” has an effect in relation to the comparison group. Although the results point to positive effects, more studies are needed to evaluate the efficiency of this type of intervention, being a point of concern for public policies in education. The second essay, on the other hand, investigated the determinants of educational aspirations in 15-year-old Latin American youth who participated in the PISA 2018 assessment. Based on a logistical model, the results reveal that individual and family characteristics are more influential than characteristics of school. Finally, they show that the influences of the analyzed covariates are associated to different degrees depending on the educational level aspired at that time by the young.